2001
DOI: 10.1023/a:1009648614566
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Given the state of the art of current language and speech technology, errors are unavoidable in present-day spoken dialogue systems. Therefore, one of the main concerns in dialogue design is how to decide whether or not the system has understood the user correctly. In human-human communication, dialogue participants are continuously sending and receiving signals on the status of the information being exchanged. We claim that if spoken dialogue systems were able to detect such cues and change their strategy acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of the error rate analysis indicated that practitioners who exhibited a relatively higher level of cue utilization were also more likely to generate error-free software code over a specified period. The simplest explanation for this result is that cue utilization facilitates error management either by focusing attention on features that signal the need to check for errors in more detail (Krahmer, Swerts, Theune, & Weegels, 2001) or, alternatively, by freeing attention resources during primary task execution for secondary meta-tasks, like online error detection (Loft et al, 2011; Loft & Remington, 2010). However, it is also possible that a third variable may independently impact a practitioner’s level of cue utilization and error management.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the error rate analysis indicated that practitioners who exhibited a relatively higher level of cue utilization were also more likely to generate error-free software code over a specified period. The simplest explanation for this result is that cue utilization facilitates error management either by focusing attention on features that signal the need to check for errors in more detail (Krahmer, Swerts, Theune, & Weegels, 2001) or, alternatively, by freeing attention resources during primary task execution for secondary meta-tasks, like online error detection (Loft et al, 2011; Loft & Remington, 2010). However, it is also possible that a third variable may independently impact a practitioner’s level of cue utilization and error management.…”
Section: Discussionmentioning
confidence: 99%